Shock therapy versus gradualism reconsidered: Lessons from transition economies after 15 years of reforms - Vladimir Popov (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
This paper starts by separating the transformational recession (reduction of output in most transition economies in the first half of the 1990s) from the process of economic growth (recovery from the transformational recession) in 28 transition economies (including China, Vietnam and Mongolia). It is argued that the former (the collapse of output during transition) can be best explained as adverse supply shock caused mostly by a change in relative prices after their deregulation due to distortions in industrial structure and trade patterns accumulated during the period of central planning, and by the collapse of state institutions during transition period, while the speed of liberalization, to the extent it was endogenous, i.e. determined by political economy factors, had an adverse effect on performance. In contrast, at the recovery stage the ongoing liberalization starts to affect growth positively, whereas the impact of pre-transition distortions disappears. Institutional capacity and reasonable macroeconomic policy, however, continue to be important prerequisites for successful performance.
Keywords: 330; Systemtransformation; Institutioneller Wandel; Deregulierung; Wirkungsanalyse; Wirtschaftskrise; Wirtschaftswachstum; Transformationsstaaten; Demokratisierung